Biochemical changes in wheat plants infected with flag smut - and M.L. CHHABRA, M.S. BENIWAL, S.S. KARWASRA (Indian Phytopathology, 2008)
Total phenols and O-dihydric phenols were more in the resistant variety WH 283 than susceptible and highly susceptible varieties at all three stages i.e. 20, 35 and 50 days after disease appearance. The decrease in total soluble sugars and reducing sugars was minimum in resistant variety WH 283 but in varieties WH 147 and WH 542 a steady decrease was observed after 20 days of symptoms appearance and the reduction was maximum after 50 days of disease appearance. Similarly, the reduction in free amino acids was more pronounced in highly susceptible variety WH 147 upto 86.81% as compared to only 37.40% in resistant variety WH 283 after 50 days of disease appearance.